Transcriptional regulation of fatty acid biosynthesis in mycobacteria - Gramajo, Hugo Cesar (2013)
The main purpose of our study is to understand how mycobacteria exert control over the biosynthesis of their membrane lipids and find out the key components of the regulatory network that control fatty acid biosynthesis at the transcriptional level. In this article we describe the identification and purification of FasR, a transcriptional regulator from Mycobacterium sp. that controls the expression of the fatty acid synthase (fas) and the 4-phosphopantetheinyl transferase (acpS) encoding genes, whose products are involved in the fatty acid and mycolic acid biosynthesis pathways. In vitro studies demonstrated that fas and acpS genes are part of the same transcriptional unit and that FasR specifically binds to three conserved operator sequences present in the fas-acpS promoter region (Pfas). The construction and further characterization of a fasR conditional mutant confirmed that FasR is a transcriptional activator of the fas-acpS operon and that this protein is essential for mycobacteria viability. Furthermore, the combined used of Pfas–lacZ fusions in different fasR backgrounds and electrophoretic mobility shift assays experiments, strongly suggested that long-chain acyl-CoAs are the effector molecules that modulate the affinity of FasR for its DNA binding sequences and therefore the expression of the essential fas-acpS operon.